Analisis Isi Mengenai Kekerasan Seksual Pada Film Like & Share - Safitri, Nur Aida; Nurlita, Ita (Wimba : Jurnal Komunikasi Visual, 2025)
ABSTRACT Currently, films have educational capabilities, namely the utilization of films in the world of education. In order to convey messages to audiences, one of the films that has a message that occurs in problems in Indonesia regarding sexual violence is a film entitled "Like & Share". This film has a lot of moral messages conveyed so that this film tells the situation about sexual violence that occurs. For this reason, the purpose of this researcher is to find out the content analysis of sexual violence in the Like & Share movie. The method used is content analysis with quantitative descriptive. The results of the discussion (1) Verbal Violence with an Overall Percentage gets 16% results with indicators of Harsh Words, Threats, Coercion, and Flirting, (2) Physical Violence with an Overall Percentage gets 20% results with indicators of Rape, Low facial expressions, Persecution, and Poking (3) Gender-Based Cyber Violence with an Overall Percentage gets 51,3% with indicators of Video Dissemination, Photo Dissemination, Pornosuara, Child Grooming, and Cyber Bullying (4) Psychological Violence with an Overall Percentage of 16% with indicators of Suicide, Self-Isolation, Uncontrolled Emotions, and Loss of Self-Confidence So that in total there are 26 scenes of Sexual Violence. Keywords: Sexual Violence, Movie, Content Analysis